Standard smoking cessation services in sites participating in the SCIMITAR+ trial for people with severe mental ill health. (February 2020) - Heron, Paul; McCloud, Tayla; Arundel, Catherine; Bailey, Della; Ker, Suzy; Li, Jinshuo; Mishu, Masuma; Osborn, David; Parrott, Steve; Peckham, Emily; Stribling, Alison; Gilbody, Simon
Abstract : Aims and method: The SCIMITAR+ trial was commissioned to evaluate the effectiveness of a bespoke smoking cessation intervention for people with severe mental ill health compared with usual services. It is difficult to define what constitutes usual care in smoking cessation services. We aimed to define what this was during the trial. Twenty-two National Health Service healthcare providers participated in a bespoke survey asking about usual care in their area. Results: All sites offered smoking cessation support; however, service provider and service type varied substantially. In some cases services were not streamlined, meaning that people received smoking cessation counselling from one organisation and smoking cessation medication from another. Clinical implications: To better implement the National Institute for Health and Care Excellence guideline PH48, clearer referral pathways need to be implemented and communicated to patients, staff and carers. People with severe mental ill health need to be able to access services that combine nicotine replacement therapy and behavioural support in a streamlined manner.